(untitled) (Nigerian Journal of Physiological Sciences, 2022)
Background: Parkinson disease (PD) and Alzheimer’s disease (AD) are progressive neurodegenerative disorders characterized by loss of selective neurons in discreet part of the brain. The peptide angiotensin II (Ang II) plays significant role in hippocampal and striatal neurons degeneration through the generation of reactive oxygen species. Blockade of the angiotensin converting enzyme or ATI receptors provides protection in animal models of neurodegenerative diseases. In the present study, the neuroprotective effect of captopril was investigated in Drosophila melanogaster model using the UAS-GAL4 system to express the synuclein and Aβ42 peptide in the flies’ neurons. Methods: The disease causing human Aβ42 peptide or α-syn was expressed pan-neuronally (elav-GAL4) or dopamine neuron (DDC-GAL4) using the UAS-GAL4 system. Flies were either grown in food media with or without captopril (1, 5, or 10µM). This was followed by fecundity, larva motility, negative geotaxis assay (climbing) and lifespan as a measure of neurodegeneration. Results: Elav-Gal4<Aβ or DDC-GAL4<α-syn flies displayed significant decrease in larva motility when compared with normal control (w1118) which was reversed by the supplementation of the media with captopril (5 or 10 mM) indicative of neuroprotection. Interestingly, supplementation of flies’ media with captopril improved climbing activity in Elav-Gal4<Aβ or DDC-GAL4<α-syn flies when compared with vehicle treated only. Moreover, flies grown on captopril caused no significant change in lifespan. Conclusion: Findings from this study confirmed the neuroprotective action of captopril in genetic or familial forms of neurodegeneration.